Increased Productivity of Packing Machines Through Implementation of Total Productive Maintenance Using the Overall Equipment Effectiveness Method Case Study of PT. GFPJ - Ferry Adhi Saputra; Mohammad Riza Rady (Jurnal Serambi Engineering, 2023)
In the world's manufacturing industry, increasing productivity is very important in fulfilling domestic and international markets as well as maintaining customer confidence. The company is trying to increase productivity in production. The fact that the packing machine is in an inefficient condition and the management is trying to implement it. in Total Productive Maintenance (TPM) to maximize the effectiveness of machine facilities in the industry. Then corrective actions are tested using the Overall Equipment Effectiveness (OEE) method, which is the calculation method used in this OEE value is determined by availability, performance and quality. The low OEE value of the packing machine at PT. GFPJ results from the availability value of = 60% for the results of the performance value of = 100% and the value of quality = 93%, it can be concluded that the OEE value obtained on the machine packing is 59.86%, while the international OEE standard is 87%, so it needs improvement. The factor that becomes a priority for improvement is the performance or performance of the machine in producing concrete, because the performance value is the lowest value of the three factors that affect the OEE value.